The Realism of English Language Competence for Students in the Tourism Industry - Nik Intan Baizura Ramsa; Rafizah binti Mohd Rawian (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2019)
The basic requisite of employability in the workforce commenced the learning institutions to handle and supervise internship training as component of study plan. Therefore, internship training is one of the necessities for the students to be equipped with the important knowledge and skills related to the workplace and their gained experience. The study was conducted to ascertain the useful English language skills for tourism course which was from the Tourism Management course in Politeknik Sandakan, Sabah, Malaysia. The research was specifically designed to focus on students’ lacks and needs of linguistic skills in order to prepare them for occupational purposes. Good English communication practice during the study will contribute more benefits to students’ education and mastery level. This research was also conducted to investigate whether what the industry needs are aligned to the students’ needs. Therefore, a needs analysis had to be done to recognize the needs of the students and the industry personnel representing the future employers of the students. The researcher sees the importance of needs analysis to be done as only 49.5 % of the polytechnic graduates were employed after they had completed their diploma course (Graduates Tracer Study, Malaysia Higher Education Statistics 2011: 118).